MODEL REGRESI UNTUK MENGANALISIS HUBUNGAN ANTARA PRODUKSI PALA DAN PRODUK DOMESTIK REGIONAL BRUTO INDONESIA - Daratullaila, Daratullaila; Ndiva, Shahnaz Tanzilla; Kurniawan, Agus; Audiyah, Tita; Ginting, Lestari Imala; Saumi, Fazrina (Jurnal Pendidikan Matematika Malikussaleh, 2025)
Nutmeg (Myristica fragrans Houtt) originates from the Maluku Islands, Indonesia, and has now spread to various countries such as Grenada, India, Sri Lanka, and the United States. As a leading commodity, nutmeg plays a crucial role in the economic growth of its producing regions in Indonesia. This study aims to analyze the relationship between nutmeg production and Gross Regional Domestic Product (GRDP) in Indonesia. The method used is a regression model. The results indicate a very strong positive correlation between nutmeg production and GRDP. The third-degree polynomial regression model, Y = 11,440,856 - 954X + 0.0430X² - 0.000000X³, with Y representing GRDP and X representing nutmeg production, is identified as the best model for explaining this relationship.